Towards carbon neutrality transition in Ghana: unveiling the synergies of ISO14001 and green governance amidst structural change and technology innovation - Miss Clare Teroviel Tergu; Isaac Sam Hayford; Jin Zhang; Jinkai Li (Discover Sustainability)
Abstract Concerns over the environment have intensified due to the worsening harm caused by climate change and ecological disasters. This has led to the implementation of radical strategies like ISO 14001 and green governance, which address the causes of pollution. This study uses panel data from 2013 to 2022 to examine the impact of ISO 14001 and green governance on CO2 emissions in Ghana amidst structural change and technological innovation while factoring in other control variables such as renewable energy, ICT and economic growth. The study utilizes the FGLS and MMQR methodologies to ensure adequate robustness checks of the results. The results assert the mitigation effects of ISO14001 and green governance on carbon emissions and therefore should be incorporated in Ghana’s structural change, renewable energy and economic growth structures. This research discovers that the green innovation pathway (technological innovation and ICT) in Ghana is more arduous since these factors exhibited either minimal or diminished association in mitigating carbon emissions. The study concludes with pragmatic recommendations for policymakers. Government may provide financial incentives, such as tax breaks, low-interest loans, to enterprises that achieve ISO 14001 certification. Sector-specific regulations should be harmonised to facilitate the development of specialised regulations for specific industries that promote cleaner production practices in accordance with ISO 14001 principles. In addition to the central government’s innovation pathway development criteria, local governments and business entities must establish supplementary technological innovation and ICT frameworks.